Does physical activity-based intervention decrease repetitive negative thinking? A systematic review - Shimeng Wang; Mingyang Lu; Xiaoxiao Dong; Yifan Xu (PLoS ONE, 2025)
Background Repetitive negative thinking (RNT) is characterized by its persistence, difficulty in control, and the tendency to focus on negative thoughts and past events. It is recognized as a key factor in the development and maintenance of mental health issues such as depression and anxiety. A growing body of research suggests that physical activity-based interventions may effectively reduce RNT. However, the extent of this effect and the mechanisms behind it remain inconsistent across studies. Methods This systematic review synthesized evidence from 19 peer-reviewed studies retrieved from PubMed, Web of Science, and other relevant databases up to December 2024. The objective was to investigate the efficacy of physical activity-based interventions in reducing RNT, with a particular focus on the influence of intervention type, duration, frequency, and intensity. Results The review found that physical activity interventions effectively reduce RNT, particularly when combined with psychological training. Combined interventions yielded greater reductions than physical activity alone. Moderate-to-high intensity exercise (30-60 min/session, 3-5 times/week) over an extended period was most effective, likely due to physiological, psychological, and social mechanisms. Single-session interventions showed limited effects, emphasizing the need for sustained engagement. Notably, interventions were more effective in individuals with depression, anxiety, or chronic stress, whereas effects in healthy individuals were smaller and more variable, suggesting that baseline symptomatology enhances intervention benefits. Conclusions This review underscores the importance of designing intervention protocols that integrate both physical and psychological components to achieve greater reductions in RNT. The findings provide empirical support for the use of combined interventions involving physical activity and psychological training as an effective strategy for managing RNT. Additionally, future research should prioritize identifying optimal intervention characteristics (e.g., type, frequency, intensity) and addressing methodological limitations, such as the inclusion of diverse participant samples and broader language coverage, to provide more comprehensive insights into effective intervention strategies. These findings have important implications for mental health interventions and offer practical guidance for developing evidence-based approaches to reduce RNT.